Development of a sustainable g-C₃N₄/CNT composite sensor for nicotine analysis in e-cigarette liquids - Reshma, Nair; Danielson Ngo, Joseph; Francesco, Spiedo; Bal, Virdee; Bhaven, Patel; Devagi, Kanakaraju; Priyanka, Ganguly (Elsevier Ltd., 2025)
The accurate quantification of nicotine in e-cigarette liquids is critical due to its potent physiological effects and potential for misuse. In this study, we report the development of a sustainable electrochemical sensor based on a composite of graphitic carbon nitride (g-C₃N₄) and multiwalled carbon nanotubes (CNTs) for the sensitive detection of nicotine. The g-C₃N₄/CNT nanocomposite was immobilised onto a glassy carbon electrode (GCE) using chitosan as a biocompatible and adhesive matrix. CNTs were employed to overcome the inherent low conductivity of g-C₃N₄, while chitosan ensured mechanical stability of the modified electrode. SEM-EDX analysis reveals g-C3N4 nanosheets interwoven with tube-like CNTs networks, with no foreign elements detected, suggesting the formation of a highly pure nanocomposite. Electrochemical characterisation revealed high selectivity and sensitivity toward nicotine under neutral pH conditions, achieving a detection limit of 0.0773 mM and a limit of quantification of 0.2343 mM. The sensor also exhibited excellent repeatability and operational stability at room temperature. The carbon based printed modified sensor also displayed similar results. Application to commercial vape samples demonstrated the practical utility of the method, with results showing strong agreement with high performance liquid chromatography (HPLC) analysis. This work highlights the promise of g-C₃N₄/CNT composites as green and effective sensing materials for nicotine monitoring in consumer products.